Rheological behavior of paraffin-alumina emulsions and their microstructural effects - Sanches, MF
Cellular ceramics were prepared by emulsification of aqueous alumina suspensions with liquid paraffin, using collagen as a shape stabilizer and a dispersant to adjust viscosity. Rheological measurements of emulsions and microstructural analysis of the sintered samples were performed. The results show that the concentration of collagen, dispersant content and stirring rate affect directly the emulsion viscosity which causes changes in porosity and average cell size. © 2016 Trans Tech Publications, Switzerland.